2004
DOI: 10.1182/blood-2003-06-1824
|View full text |Cite
|
Sign up to set email alerts
|

The FIP1L1-PDGFRα fusion tyrosine kinase in hypereosinophilic syndrome and chronic eosinophilic leukemia: implications for diagnosis, classification, and management

Abstract: Idiopathic hypereosinophilic syndrome (HES) and chronic eosinophilic leukemia (CEL) comprise a spectrum of indolent to aggressive diseases characterized by unexplained, persistent hypereosinophilia. These disorders have eluded a unique molecular explanation, and therapy has primarily been oriented toward palliation of symptoms related to organ involvement. Recent reports indicate that HES and CEL are imatinib-responsive malignancies, with rapid and complete hematologic remissions observed at lower doses than u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
205
1
18

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(227 citation statements)
references
References 174 publications
3
205
1
18
Order By: Relevance
“…Recent studies have suggested a pivotal role for imatinib mesylate in the treatment of HES [16]. A proportion of patients with HES responded to low doses of imatinib mesylate, although some patients were resistant and the duration of the response is still unknown [16,17]. The rapid response to therapy would make imatinib mesylate an attractive drug to improve the clinical condition of the patient, even of those who plan to proceed to allogeneic stem-cell transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested a pivotal role for imatinib mesylate in the treatment of HES [16]. A proportion of patients with HES responded to low doses of imatinib mesylate, although some patients were resistant and the duration of the response is still unknown [16,17]. The rapid response to therapy would make imatinib mesylate an attractive drug to improve the clinical condition of the patient, even of those who plan to proceed to allogeneic stem-cell transplant.…”
Section: Discussionmentioning
confidence: 99%
“…The patient also showed most of the principal clinical features of Löffler endocarditis, such as weight loss, fever, cough, and congestive heart failure. Since the World Health Organization classification recommends the exclusion of any cause of secondary eosinophilia like malignant or autoimmune diseases, parasitic disease, allergy, or drug reactions in the clinical workup of patients with Löffler endocarditis eosinophilia 13,22 , we explored any other cause that might explain the hypereosinophilia. Stool examinations were negative, and there was no sign of a malignancy, allergy, or drug reaction.…”
Section: Discussionmentioning
confidence: 99%
“…CEL is mostly caused due to FIP1-like-1 platelet-derived growth factor-alpha (FIP1L1-PDGFRa) fusion gene (Gotlib et al, 2004). Eosinophils include a variety of granulocytes, such as neutrophils and basophils, with granules and polymorphous nuclei; they account for approximately 1% to 5% of white blood cells (<1,500/µL) in normal individuals.…”
Section: Introductionmentioning
confidence: 99%